Neonatal focal temporal lobe or atrial wall haemorrhagic infarction. Issue 3 (1st November 1999) - Govaert, Paul; Smets, K; Matthys, E; Oostra, A
Abstract : AIMS: To describe two variants of infarction within the temporal lobe, associated with local matrix bleeding and mild to moderate intraventricular haemorrhage. METHODS: The files of 10 neonates, extracted from a sonographic study of 560 very low birthweight infants conducted between 1993 and 1997, were retrospectively examined. RESULTS: Seven lesions were located in the middle to posterior area of the temporal lobe, three others faced the atrium. All except two of those with a temporal site were VLBW infants with hyaline membrane disease. Except for one fatal case, intraventricular bleeding was mild to moderate. Computed tomograms or magnetic resonance imaging were used to illustrate the haemorrhagic nature of three lesions. Survivors of this so far undescribed entity who were followed up for more than 18 months did not have a uniform type of cerebral palsy but some scored in the low normal range on the Bayley Mental Development Index. One girl developed temporal lobe epilepsy. CONCLUSIONS: This pattern of injury seems to be one of venous infarction associated with temporal or para-atrial matrix haemorrhage. The temporal site fits the picture of venous infarction within the area drained by the inferior ventricular vein. A less constant lateral atrial vein, either draining into the basal or internal cerebral vein, is probably involved in the para-atrial lesion. Sonography may be the only practical tool currently available for detection in life.